Synthesis of fluorescent dye and hydrogel therefrom for detection of glucose - Vaitusionak, Aliaksei A.; Sokolnikova, Ekaterina V.; Baravoi, Hleb S.; Minakov, Grigory I.; Kostjuk, Sergei V. (Journal of the Belarusian State University. Chemistry, 2025)
As a result of the study, an five-step procedure for the synthesis of a glucose-sensitive fluorescent dye consisting of two boronic acid fragments and an anthracene fragment was developed. Fluorescent hydrogel was then prepared based on the synthesised dye. It was shown that the fluorescence intensity of the synthesised dye directly depends on the concentration of glucose, the increase of which leads to fluorescence enhancement. The synthesised fluorescent hydrogel can be used for fabrication of subcutaneous glucose sensor.